The Impact of Obstructive Jaundice on Quality of Life (Medical Forum Monthly, 2022)
Objective: The purpose of the study is to assess the effects of gall bladder disease patients to maintain their quality of life of having obstructive jaundice.Study Design: Case control study.Place and Duration of Study: This study was conducted at the Civil Hospital’s Outpatient Department of General Surgery, Unit-1, and Karachi from 18th December 2018 to June 2019.Materials and Methods: It was conducted on 195 patients of both genders age 20yrs – 80yrs diagnosed with obstructive jaundice and underwent for biliary patenting. In those patients we assessed quality of life with the short form-36 (SF-36) which includes 8 domains. SPSS version-21 was used to analyze the data.Results: The results of our study revealed statistically highly significant effect of cholelithiasis, chronic cholecystitis and gall bladder polyp on quality of life of obstructive jaundice patients (p<0.001*). Also patients with such diseases also had a significantly lower SF-36quality of life scores for both overall and in all eight individual domains than those patients who did not have those diseases, whereas it also indicated that the existence of gall bladder carcinoma in patients with obstructive jaundice didn’t have a statistically significant effect on their quality of life (p>0.05).Conclusion: Our study concludes that quality of life of those patients who were suffering from the benign causes of obstructive jaundice; such as cholelithiasis, chronic cholecystitis and gall bladder polyp were more significantly improved after therapy, whereas patients with gall bladder carcinoma had a worst effect on quality of life for both the genders.